Pengaruh Pemberian Ekstrak Tanaman Sirih Cina (Peperomia pellucida L. Kunth) Terhadap Penurunan Kadar Glukosa Darah Pada Mencit (Mus Musculus) - Nastain Nurfatanah Saharun; Wa Ode Salma; Febriana Muchtar (Program Studi S2 Kesehatan Masyarakat Universitas Halu Oleo, 2025)
Diabetes mellitus is one of the most common chronic diseases in the world and is the fourth leading cause of death in various developing countries. This disease includes a group of complex metabolic disorders characterized by chronic hyperglycemia. This condition occurs due to damage to pancreatic beta cells that inhibit the production of the hormone insulin, which plays an important role in regulating blood glucose levels. This disorder can include problems with insulin secretion, insulin function, or a combination of both as anabolic hormones. The Chinese betel plant has secondary metabolite compounds, namely alkaloids, flavonoids, saponins, tannins, and steroids that can reduce blood glucose levels in mice. The purpose of this study was to determine the effect of administering Chinese betel plant extract (Peperomia pellucida L. Kunth) on reducing blood glucose levels in mice (Mus musculus). This study used a laboratory experimental research type with a true experimental research design with a pretest-posttest control group design. The results of the study obtained were the effect of administering Chinese betel plant extract (Peperomia pellucida L. Kunth) on reducing blood glucose levels in mice (p <0.05). The average decrease in blood glucose levels in mice, namely the positive control group 136.286 mg/dL, treatment group (1) 176.429 mg/dL, and treatment group (2) 150.286 mg/dL. Chinese betel plant extract (Peperomia pellucida L. Kunth) can reduce blood glucose levels in mice for 14 days